Analisis Lompatan Katak dan Manusia dalam Tinjauan Biomekanika - Nadila Putri Sawhana (Progressive Physics Journal, 2020)
Biomechanics is applied physics with implementing mechanics concepts in biological system. Biomechanics studies the movements of the whole body on living organism. The purpose of our research was to know the differences of jump between frog and human in the biomechanical field. In our experiment it was used the samples of 10 frogs and 10 humans by college students of physics department, Faculty of Mathematics and Natural Science, with randomly selected. The results of the research were: first, the ratios of the jump distance to mass of frog bodies were bigger than those of human bodies; second, the effective angles of the frog’s furthest jumps were (36.45 ± 0.027)° and those of human’s furthest jumps were (60.45 ± 0.002)°. The first result indicated that the frog’s tendon was more elastic than the human’s tendon.